The Role of Teacher–Apprentice Relations in Didactic Works in Society Development - Izbullaeva Gulchekhra Valerievna (International Journal on Integrated Education, 2023)
This article deals with the importance of social relations in the development of society, the content of the education of an enlightened person, the relationship between a teacher and a student in the didactic works of enlightened thinkers who lived in Central Asia at the end of the 12th century – the first half of the 14th century. The main tasks that serve to educate an enlightened person: striving for continuous enlightenment; desire for knowledge; conducting education in an orderly manner; create enlightenment; complete attachment to enlightenment; enlightenment of the environment; connecting the purpose and profession with enlightened people; It is based on achieving a special quality called enlightenment. Also, in the teacher–student relationship, the teacher is the one who is on the right path; believer, guide to the right path; correcting, reforming, always aware of the behavior of the student, literate, «khuvaidoyu nihan», i.e. the revealer of all your innermost secrets, the giver of knowledge, is embodied in a kind word. It was emphasized that the student should not be suspicious of any activity of the teacher, should listen to his words and perform his actions without words and acquire knowledge. It is expressed in mutual respect and understanding in the relationship between teacher and student.